Impact of different plant growth promoters on the physicochemical properties, volatile compounds, and antioxidant capacity of Allium ramosum flowers - Xu, Rui; Qiu, Mengli; Chang, Youchuan; Yan, Ziyuan; Li, Zichan; Han, Xu; Hu, Gang; Liu, Guixia (Frontiers in Plant Science, 2025)
Plant growth promoters regulate the production of bioactive compounds within plants, stimulating the accumulation of aromatic substances. However, the potential mechanisms by which amino acid fertilizers (Feihong Fertilizer Co., Ltd., main components: organic matter 13.9%, total nitrogen 2.3%, total phosphorus anhydride 0.2%, total potassium oxide 0.3%, chlorine 0.1%, sodium less than 0.1%) and algal extracts (Hangzhou Qingyang Technology Co., Ltd., main components: calcium+magnesium ≥100g/L, marine minerals ≥ 5%), influence the characteristic flavor compounds and antioxidant activity of Allium ramosum flowers remain unclear. Amino acid fertilizers and algal extracts were applied in combination with different substrates to investigate their effects on the dry weight, fresh weight, inflorescence stem height, corolla diameter, total ascorbic acid content, glutathione content (GSH), proline content, polyphenol content, flavonoids content, flavones content, soluble protein content, soluble sugars content, antioxidant activity, and volatile compounds of Allium ramosum flowers. We found that amino acid fertilizers and algal extracts in combination with compound microbial fertilizers significantly increased the content of polyphenols and flavonoids (The increases were 56.1% and 57.1%, respectively), total ascorbic acid content and glutathione content (GSH)(The increases were 154.5% and 58.2%, respectively), and reduced the content of malondialdehyde (MDA) and superoxide anion (O2• −). Additionally, these treatments significantly improved the 2,2-diphenyl-1-picrylhydrazyl radical scavenging rate, ABTS scavenging rate, iron reducing antioxidant power, superoxide anion radical scavenging rate (SASR), hydroxyl radical scavenging activity (HRSC), POD, SOD, and PPO activity(The increases were 11.6%, 63.8%, 173%, 105%, 53%, 56.1%, 56.2%, and 71.8%, respectively), and increased the antioxidant activity and volatile compound content of Allium ramosum flowers, thereby improving their postharvest quality and shelf life. In summary, the application of amino acid fertilizers and algal extracts had a positive effect on the growth, quality, antioxidant activity, and flavor of Allium ramosum flowers, thereby increasing their commercial value.